Socio-environmental impacts of non-native and transplanted aquatic mollusc species in South America: What do we really know? - Carranza, Alvar (2023)
The impacts of biological invasions remain poorly known for some habitats, regions and taxa. To date, there has been no comprehensive effort to review and synthesize the impacts of invasive mollusc species in South America. In this paper, we provide a synoptic view on what is known on documented socio-ecological impacts of aquatic no-native mollusc species (NNMS) and transplanted mollusc species (TMS) from South America. An expert group involving malacologists and taxonomists from different countries, the “South America Alien Molluscs Specialists” (eMIAS), shared and summarized the scientific literature, databases, and published and unpublished information on confirmed impacts of NNMS and TMS in South America. Three broad categories, non-mutually exclusive were used as a framework: “Environmental/Biodiversity impacts”, “Economic and social effects”, and “Human health impacts”. Some 21 NNMS and seven TMS have documented impacts on at least one of those three categories. We encourage targeting the less known areas of research, such as economic valuation of human health (and veterinary) impacts attributable to NNMS or TMS and expand our knowledge of environmental impacts for the species listed in this study.